2011
DOI: 10.4049/jimmunol.0904135
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of Regulatory Capacity of CD4+CD25+ Regulatory T Cells Mediated by Dendritic Cell Polarization and Hyperthyroidism in Graves’ Disease

Abstract: Graves’ disease (GD) is one of the most common autoimmune diseases. The immune dysfunction in GD involves the generation of thyroid-stimulating hormone receptor (TSHR) autoantibodies that presumably arise consequent to interactions among dendritic cells (DCs), T cells, and regulatory T (Treg) cells. However, the immunological mechanisms of interactions between them that lead to the induction and regulation of this autoimmune disease are poorly defined. In this study, we investigated whether DCs are the main ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
83
4
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(96 citation statements)
references
References 58 publications
5
83
4
4
Order By: Relevance
“…Interestingly, also in a study analysing peripheral blood DCs in AITD pDC (but not the whole DC) population was significantly increased in untreated hyperthyroid GD patients as compared with healthy subjects, euthyroid GD and euthyroid HT patients. Moreover, the expression of CD80, CD86, and CD40 was slightly increased in untreated GD patients, comparing with healthy subjects [46]. The pDC/DC ratio was considerably higher in untreated GD (as juxtaposed to other AITD patients) and correlated negatively with the count of CD4 + CD25 + FOXP3 + population of peripheral blood Tregs.…”
Section: Cd8amentioning
confidence: 78%
See 1 more Smart Citation
“…Interestingly, also in a study analysing peripheral blood DCs in AITD pDC (but not the whole DC) population was significantly increased in untreated hyperthyroid GD patients as compared with healthy subjects, euthyroid GD and euthyroid HT patients. Moreover, the expression of CD80, CD86, and CD40 was slightly increased in untreated GD patients, comparing with healthy subjects [46]. The pDC/DC ratio was considerably higher in untreated GD (as juxtaposed to other AITD patients) and correlated negatively with the count of CD4 + CD25 + FOXP3 + population of peripheral blood Tregs.…”
Section: Cd8amentioning
confidence: 78%
“…Furthermore, pDCs obtained from untreated GD patients revealed significant ability to suppress inhibitory action of regulatory T cells and in this way promoted the proliferation of effector T cells in co-cultures. Importantly, such pronounced Tregs-inhibitory activity was not observed with none of the cDC populations nor with pDCs derived from euthyroid patients [46].…”
Section: Cd8amentioning
confidence: 99%
“…The analysis of transcriptomic profiles of thyroid tissue in different stages of Graves' disease (GD) revealed progressive accumulation of changes in the expression of numerous immune factors, among them -associated with pDCs [18]. On the cellular level, it has been shown that the decrease of regulatory T cells (Tregs) observed in peripheral blood of untreated GD patients was associated with elevated pDC/cDC proportion [19]. Moreover, in co-culture experiments the authors demonstrated that pDCs (but not cDCs) derived from untreated GD patients efficiently inhibited immunosuppressive activity of Tregs [19].…”
Section: Discussionmentioning
confidence: 99%
“…On the cellular level, it has been shown that the decrease of regulatory T cells (Tregs) observed in peripheral blood of untreated GD patients was associated with elevated pDC/cDC proportion [19]. Moreover, in co-culture experiments the authors demonstrated that pDCs (but not cDCs) derived from untreated GD patients efficiently inhibited immunosuppressive activity of Tregs [19]. Most recently, Leskela and colleagues [14] have shown decreased percentage of pDCs in PBMCs obtained both from patients with HT and GD, as well as disease-and disease-stage specific changes in immunoregulatory phenotype of pDCs.…”
Section: Discussionmentioning
confidence: 99%
“…The situation in Greaves' autoimmune hyperthyroidism is better understood. There, autoantibodies to the overexpressed thyroidstimulating hormone receptor (TDHR) and decreased Treg cells in number and function cooperate with IFNαproducer plasmacytoid DCs that cause apoptotic death of the Treg cells (187). It is still unclear what inflammatory process activates the plasmacytoid DCs in the first place: may be an endogenous retrovirus?…”
Section: Papillary Carcinoma Cells Of the Thyroid Release Inflammatormentioning
confidence: 99%